The Devotion and Promotion of Stigmatics in Europe, c. 1800-1950 Between Saints and Celebrities - Van Osselaer, Tine (Numen Book Series, 2020)
In the nineteenth century a new type of mystic emerged in Catholic Europe. While cases of stigmatisation had been reported since the thirteenth century, this era witnessed the development of the 'stigmatic': young women who attracted widespread interest thanks to the appearance of physical stigmata. To understand the popularity of these stigmatics we need to regard them as the 'saints' and religious 'celebrities' of their time. With their 'miraculous' bodies, they fit contemporary popular ideas (if not necessarily those of the Church) of what sanctity was. As knowledge about them spread via modern media and their fame became marketable, they developed into religious 'celebrities'. Readership: All interested in European religious history of the nineteenth and early twentieth century, those who have an interest in cultural history and/or celebrity studies.